Sacral nerve stimulation for faecal incontinence: medium‐term follow‐up from a single institution. Issue 6 (19th May 2016) - Patton, Vicki; Abraham, Earl; Lubowski, David Z.
Abstract : Background: Most studies on sacral nerve stimulation (SNS) are either single‐centre with small numbers of patients or multi‐centre studies. We present the medium‐term follow‐up results from a single centre for 127 patients undergoing SNS. Methods: Consecutive patients treated with SNS for faecal incontinence had preoperative baseline St Mark's continence scores, faecal incontinence quality of life (FIQL) measures and anorectal physiology studies. Follow‐up was a postal questionnaire concerning continence, FIQL, patient‐perceived change in bowel control (−5 to +5 where 0 is no change), overall satisfaction (0–10 visual analogue scale) and use of medications. Results: A total of 166 patients underwent temporary nerve stimulation testing, of which 112 progressed to a permanent implantable pulse generator (IPG). Fifteen received an IPG without the testing phase, hence 127 patients in total. Fourteen had the IPG removed, four were deceased, leaving 109 for assessment; 91 (83%) responded to the survey. Mean follow‐up was 2.7 years (range: 2 months–8.5 years). Mean baseline St Mark's continence score was 14.4, and mean follow‐up score was 10.3 ( P  < 0.01). FIQL improved in all domains ( P  < 0.001). Patient‐reported improved bowel control mean score was +3.2 (95% CI: 2.9, 3.55). Median satisfaction score was 8.0 (range: 0–10). Complications included 17 lead dislodgements, seven superficial infections, five infections requiring surgery and five repositioning of a rotated IPG. Thirty‐two patients used loperamide and 34 used fibre supplements. Conclusion: In this observational study, limited by the absence of a placebo control group, SNS significantly improved continence and quality of life, and patient satisfaction was high.